2021
DOI: 10.1038/s43016-021-00348-z
|View full text |Cite
|
Sign up to set email alerts
|

Modern slavery risk assessment

Abstract: Agrifood supply chains have high risks of labor exploitation. Around two million people work under conditions of modern slavery and forced labor -as the most extreme end of the labor exploitation continuum -in this sector worldwide (ILO and Walk Free Foundation, 2017). So far, the concept of sustainable food system has focused on issues of food security, nutrition for society and consumer health in a way that planetary boundaries are not crossed but it has neglected parts of the social dimension of sustainabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, while cocoa from Cote d’Ivoire and Ghana, cashews from Vietnam, and tomato products from Mexico exported to the United States have repeatedly been flagged as high risk for labour abuses 16 , 17 (which we also identified), we found disproportionately high levels of risk in meat products produced in the United States. Because risk responses are determined by stakeholders’ perceptions of perceived risks 18 , methodological innovations that move beyond commodity case studies (which are important and necessary, but narrow in purview) may help eliminate geographic and commodity blind spots in supply chains. Our method can support more dynamic risk modelling 19 and monitoring 20 in supply chains without relying on intermittent social audits that have been critiqued for their inability to detect forced labour 21 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, while cocoa from Cote d’Ivoire and Ghana, cashews from Vietnam, and tomato products from Mexico exported to the United States have repeatedly been flagged as high risk for labour abuses 16 , 17 (which we also identified), we found disproportionately high levels of risk in meat products produced in the United States. Because risk responses are determined by stakeholders’ perceptions of perceived risks 18 , methodological innovations that move beyond commodity case studies (which are important and necessary, but narrow in purview) may help eliminate geographic and commodity blind spots in supply chains. Our method can support more dynamic risk modelling 19 and monitoring 20 in supply chains without relying on intermittent social audits that have been critiqued for their inability to detect forced labour 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The agricultural sector has a high risk of labour exploitation due to its high labour intensity and relatively low skill requirements (Gold et al, 2021). In agriculture, more than two million people work under conditions of modern slavery worldwide (ILO and Walk Free Foundation, 2022).…”
Section: Literature and Theorymentioning
confidence: 99%
“…Drawing on social life cycle assessment (S-LCA), Blackstone et al (2021) have evaluated how specific US retail supply chains of fruits and vegetables are affected by forced labour risks, thereby identifying supply chains where priority intervention is required by business, authorities, and civil society. It was found that major forced labour risks in food supply are associated with US domestic supply chains; this shows that labour exploitation is no remote problem located in far-off regions, but also affects the very countries that generate its demand (Gold et al, 2021).…”
Section: Literature and Theorymentioning
confidence: 99%